Delay in surgical treatment of patients with hilar cholangiocarcinoma: does time impact outcomes?. Issue 5 (26th August 2013) - Ruys, Anthony T.; Heuts, Simon G.; Rauws, Eric A.; Busch, Olivier R. C.; Gouma, Dirk J.; van, Thomas M.
Abstract Background Substantial time elapses before patients with hilar cholangiocarcinoma (HCC) receive surgical treatment because of time‐consuming preoperative staging and other interventions, including biliary drainage and portal vein embolization. Prolonged times potentially lead to unresectability and the formation of metastases, yet these issues have not been investigated previously in HCC. This study aimed to evaluate the time between onset of symptoms and the provision of ultimate treatment in patients with HCC and the impact of the length of time on outcomes. Methods Delays in the treatment of consecutive patients with HCC were evaluated by contacting general practitioners (GPs) and extracting data from hospital files. Time periods were correlated with resectability, occurrence of metastasis, tumour stage and survival using logistic and Cox regression analyses. Results Treatment times in 209 consecutive HCC patients were evaluated. The median time from first GP visit until presentation at the tertiary centre was 35 days. Time until treatment was longer when initial symptoms did not include jaundice (non‐specific symptoms, P < 0.001). Duration of workup and preoperative biliary drainage at the tertiary centre prior to final surgical treatment resulted in an additional median time of 74 days. No correlation was found between treatment time in weeks and resectability [odds ratio (OR) 1.010, 95% confidence interval (CI) 0.985–1.036], metastasis (OR = 0.947, 95% CI 0.897–1.000), tumour stage (OR = 1.006, 95% CI 0.981–1.031) or survival in resected patients (hazard ratio = 0.996, 95% CI 0.975–1.018). Conclusions The time that elapses between the presentation of symptoms and final treatment in patients with HCC is substantial, especially in patients with non‐specific symptoms. This time, however, does not affect resectability, metastasis, tumour stage or survival, which suggests that preoperative optimization should not be omitted because of potential delays in treatment.